Comparative Brain and Central Nervous System Tumor Incidence and Survival between the United States and Taiwan Based on Population-Based Registry - Chien, Li-Nien; Gittleman, Haley; Ostrom, Quinn T.; Hung, Kuo-Sheng; Sloan, Andrew E.; Hsieh, Yi-Chen; Kruchko, Carol; Rogers, Lisa R.; Wang, Ye-Fan Glavin; Chiou, Hung-Yi; Barnholtz-Sloan, Jill S. (Frontiers in Public Health, 2016)
Purpose: Reasons for worldwide variability in the burden of primary malignant brain and central nervous system (CNS) tumors remain unclear. This study compares the incidence and survival of malignant brain and CNS tumors by selected histologic types between the United States (US) and Taiwan. Methods: Data from 2002 to 2010 were selected from two population-based cancer registries for primary malignant brain and CNS tumors: the Central Brain Tumor Registry of the United States (CBTRUS) and the Taiwan Cancer Registry. Two registries had similar process of collecting patients with malignant brain tumor and the quality of two registries were comparative. The age-adjusted incidence rate (IR), IR ratio, and survival by histological types, age and gender were used to study regional differences. Results: The overall age-adjusted IRs were 5.91 per 100,000 in the US and 2.68 per 100,000 in Taiwan. The most common histologic type for both countries was glioblastoma with a 12.9% higher proportion in the US than in Taiwan. Glioblastoma had the lowest survival rate of any histology in both countries (US 1-year survival rate = 37.5%; Taiwan 1-year survival rate = 50.3%). The second largest group was astrocytoma, excluding glioblastoma and anaplastic astrocytoma, with the distribution being slightly higher in Taiwan than in the US. Conclusions: Our findings revealed differences by histological type and grade of primary malignant brain and CNS tumors between two sites.